Parents’ Perspectives on School Transitions: Challenges and Strategies on Transition from Preschool to Primary School for Equitable Education - Nibrosurrahman, Maryam; Kurniati, Euis (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
The transition from preschool to primary school is a critical period in a child's development, involving significant changes in environment, routines, and academic demands. Parental involvement plays a key role in ensuring a smooth transition; however, many parents experience anxiety due to misconceptions about literacy expectations and limited communication from schools. This study explores parents' perspectives on school transition, identifies challenges they face, and examines their involvement in supporting their children's adjustment. Using a qualitative phenomenological approach, this study conducted in-depth interviews with four parents of first-grade students from different public and private elementary schools in Cimahi City. Observations at one public elementary school complemented the interview data. Thematic analysis was applied, and findings were interpreted using Bronfenbrenner’s ecological theory to understand how various social and environmental systems influence school transitions. Findings reveal that parental concerns about school readiness often stem from misunderstandings about academic expectations and inadequate school communication. Fathers' involvement in the transition process was notably limited, with mothers playing the primary role in preparation and support. Strengthening collaboration between parents and schools is essential for an effective transition. According to Bronfenbrenner’s model, successful transitions depend on interactions across subsystems, including the microsystem, mesosystem, exosystem, and macrosystem. This study enhances understanding of parental roles in school transitions and provides recommendations for educators and policymakers to design inclusive transition programs. Future research could expand sample sizes and further investigate fathers' participation to develop targeted interventions. Encouraging stronger school communication policies and fostering collaboration between early childhood and primary educators can optimize parental involvement and support children’s transition success.